Effect of acclimatisation in physiological parameters of high-yielding dairy cows - Silva, Flávio (2022)
Heat stress alter the physiological status and the energetic balance in high producing animals. Acclimatisation is a thermoregulatory adaptation to heat stress with detrimental effects on productivity. We hypothesised that high-yielding dairy cows (HP; ≥9,000 kg – 305 days in milk; n=7) suffer a more significant influence of elevated environmental temperatures than low-yielding cows (LP; <9,000 kg – 305 DIM; n=6). Physiological and milk composition data was collected in summer (5 days with mean environmental temperatures of 23.5 °C – heat stress) and winter (5 days with mean environmental temperature of 6.6 °C – thermoneutrality). Respiratory rate (HP: 63.95±12.35; LP: 64.34±13.67 movements/minute), sweat rate (HP: 77.70±48,90; LP: 75.86±45.02 g/m2/h) rectal temperature (HP: 38,87±0,72; LP: 38,76±0,63 °C) were significantly higher in summer than in winter across both groups, indicating a response to mild heat stress. Plasma triiodothyronine levels were lower in HP than LP in summer, indicating a higher degree of acclimatisation in HP cows. Haematocrit and hemoglobulin were significantly higher in summer but not different between groups. Regarding milk production, HP produced more milk than LP, but the difference between groups was shorter in summer than winter (17.90% and 22,30%, respectively). There were no differences in milk parameters within groups, except urea in the summer period (293.62 mg/kg and 253.69 mg/kg for HP and LP, respectively). Milk fat and protein were significantly lower in summer than winter. These results showed that elevated environmental temperatures alter the physiological status in both groups. Cows with different milk yield had similar first responses to heat stress. However, during the acclimatisation process, HP decreased metabolism rate while alterations in nitrogen pathways were observed.